The financialization of mass wealth, banking crises and politics over the long run. (December 2019) - Chwieroth, Jeffrey M; Walter, Andrew
The co-evolution of democratic politics and mass, financialized wealth has destabilized highly integrated financial systems and the socio-political underpinnings of neoliberal policy norms at domestic and global levels. Over the long run, it has increased the political pressure on governments to undertake bailouts during major banking crises and, by raising voters' attentiveness to wealth losses and distributional inequities, has sharply raised the bar for government performance. The result has been more costly bailouts, greater political instability and the sustained politicization of wealth cleavages in crisis aftermaths. We underline the crucial importance and modernity of this phenomenon by showing how the high concentration of wealth in pre-1914 Britain and America among elites was associated with limited crisis interventions and surprisingly tranquil political aftermaths. By contrast, the 2007–2009 crises in both countries epitomise the political dilemmas facing elected governments in a new world of mass financialized wealth and the impact on political polarization and democratic politics. We show that these dilemmas were embryonic in the interwar period and highlight how the evolutionary forces shaping policy and political outcomes reveal the importance of time, context and the effects of long cycles in the world economy and global politics.